Has_circ_CCNB1 and has_circ_0009024 function as potential biomarkers for the diagnosis of type 2 diabetes mellitus. Issue 10 (6th July 2020) - Chen, Xiangfei; Yin, Jingjing; Zhang, Fang; Xiao, Tiantian; Zhao, Ming
Abstract: Circular RNAs (circRNAs) have been reported to be associated with various diseases, including type 2 diabetes mellitus (T2DM). The aim of present study was to investigate the clinical value of has_circ_CCNB1 and has_circ_0009024 in T2DM. Serum samples from patients with T2DM (n = 166) and healthy volunteers (n = 166) were recruited. Then, real‐time quantitative reverse transcription‐polymerase chain reaction (RT‐qPCR) analysis and enzyme‐linked immunosorbent (ELISA) assays were conducted to detect the expression levels of circRNAs and inflammatory factors. Furthermore, the correlation analysis and receiver operating characteristic (ROC) curve were used to evaluate diagnostic accuracy. From the results, circ_CCNB1 was significantly increased while circ_0009024 was decreased in serum samples from T2DM patients. Moreover, has_circ_CCNB1 was positively correlated with glucose (GLU), glycosylated hemoglobin (GHb), interleukin 6 (IL‐6), and tumor necrosis factor‐α (TNF‐α) while has_circ_0009024 was negatively correlated with them. Importantly, the AUC of has_circ_CCNB1 and has_and circ_0009024 was 0.9255 (95% CI = 0.8909‐0.9601) and 0.9592 (95% CI = 0.9381‐0.9803), while the AUC of combinative curve is 0.8875 (95% CI = 0.8204‐0.8547). In a word, has_circ_CCNB1 and has_circ_0009024 may exhibit as potential biomarkers for the diagnosis of T2DM. Abstract : Circular RNAs (circRNAs) have been reported to be associated with various diseases, including type 2 diabetes mellitus (T2DM). The aim of present study was to investigate the clinical value of has_circ_CCNB1 and has_circ_0009024 in T2DM. In the present study, circ_CCNB1 was significantly increased while circ_0009024 was decreased in serum samples from T2DM patients. Moreover, has_circ_CCNB1 was positively correlated with glucose (GLU), glycosylated hemoglobin (GHb), interleukin 6 (IL‐6), and tumor necrosis factor‐α (TNF‐α) while has_circ_0009024 was negatively correlated with them. Importantly, the AUC of has_circ_CCNB1 has_and circ_0009024 were 0.9255 (95% CI = 0.8909~0.9601) and 0.9592 (95% CI = 0.9381~0.9803), while the AUC of combinative curve is 0.8875 (95% CI = 0.8204~0.8547). In a word, has_circ_CCNB1 and has_circ_0009024 may exhibit as potential biomarkers for the diagnosis of T2DM.